Therapeutic Use of Cannabinoids: Clinical Overview and Recent Updates - Altun, Beril (Current Research in Pharmacy and Pharmaceutical Sciences II-2024, 2024)
Cannabinoids, regardless of their structure or origin, refer to chemical substances that act on cannabinoid receptors and produce pharmacological effects similar to Δ9-tetrahydrocannabinol (Δ9-THC), the main psychoactive ingredient of the Cannabis sativa plant. Cannabinoids, which act on the endocannabinoid system, are thought to have a potential therapeutic value in a variety of diseases and conditions due to their involvement in vital processes such as appetite, nausea, vomiting, pain sensitivity, mood and memory. To date, cannabinoids have been approved for certain indications by the United States Food and Drug Administration (FDA): refractory epilepsy (Lennox–Gastaut syndrome, Dravet syndrome, and tuberous sclerosis complex), spasticity and neuropathic pain in multiple sclerosis (MS), Acquired Immune Deficiency Syndrom (AIDS)-related cachexia, and chemotherapy-induced nausea and vomiting. According to pre-clinical studies, cannabinoids are also promising for a wide range of indications such as fibromyalgia, post-traumatic stress disorder, insomnia, anxiety, cancer, and cancer-related pain. Cannabinoids are being explored as an anticancer agent in different types of cancer due to increasing evidence for their antiproliferative and antitumor effects. Scientific research that will reveal the therapeutic potential of cannabinoids, cannabinoid type/ratio, and efficacious dosage forms on an evidence-based approach are needed for non-approved indications including cancer. Foremost, the elimination of legal barriers in front of scientific research on cannabinoids will ease towards this goal. In this chapter, it is aimed to summarize the therapeutic use of cannabinoids, prospects for novel indications, and ongoing clinical trials to provide a comprehensive overview on the current state of knowledge.